Gait characterization for patients with orthostatic tremor. (February 2020) - Opri, Enrico; Hu, Wei; Jabarkheel, Zakia; Hess, Christopher W.; Schmitt, Abigail C.; Gunduz, Aysegul; Hass, Chris J.; Okun, Michael S.; Wagle Shukla, Aparna
Abstract: Introduction: Orthostatic tremor (OT) patients frequently report gait unsteadiness with the advancement of disease; however, there is little understanding of its physiology. We sought to examine in OT, the spatial and temporal characteristics of gait, and the relationship with tremor physiology. Methods: Gait parameters for OT (n = 16) were recorded with an instrumented Zeno walkway system. All participants complained of gait unsteadiness, especially during slow walking. In a subset of OT, recordings were synchronized with a wireless EMG system for tremor assessment and feet pressure recording. Gait assessments were performed at self-selected habitual, fast, and slow speeds. Results: Compared to data available for an age- and sex-matched healthy controls, OT patients had a significantly reduced step length, increased step width, and increased gait variability (p < 0.0001). Tremor discharges related to OT were consistently recorded across three different speeds of walking. These discharges persisted through all phases of the gait cycle, including the swing phase when the limb was not weight-bearing. The highest tremor amplitude was recorded in the single support phase, followed by double support, and least during the swing phase. Conclusion: OT patients have distinct gait abnormalities similar to cerebellar disorders. Tremor discharges from the non-weight bearing leg in the swing phase suggests that muscle contractions, even when occurring without resistance, contribute to OT generation. Highlights: Distinct gait abnormalities characterize orthostatic tremor (OT). These abnormalities include reduced step length, increased step width, and increased gait variability. Gait abnormalities are similar to those seen in cerebellar disorders suggesting cerebellum as a pathogenic source for OT. Tremor can persist during all phases of the gait cycle, including the swing phase when the leg is off the ground. Tremor persistence in the non-weight bearing leg implies factors besides weight-bearing for the generation of tremor.